2008
DOI: 10.1080/03640210802035365
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual Processing Affects Conceptual Processing

Abstract: According to the Perceptual Symbols Theory of cognition (Barsalou, 1999), modality-specific simulations underlie the representation of concepts. A strong prediction of this view is that perceptual processing affects conceptual processing. In this study, participants performed a perceptual detection task and a conceptual property-verification task in alternation. Responses on the property-verification task were slower for those trials that were preceded by a perceptual trial in a different modality than for tho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
110
2
3

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(126 citation statements)
references
References 34 publications
10
110
2
3
Order By: Relevance
“…By highlighting the contrast between internal and external perspectives, the present findings extend previous work on the role of perspective in language comprehension, which explored how people construct different perspectives when understanding external events (Borghi et al, 2004;Brunyé et al, 2009;Horton & Rapp, 2003;Morrow et al, 1987;Spivey & Geng, 2001;Wu & Barsalou, 2009). Moreover, by introducing an internal perspective, the present findings extend previous work on switching effects that has mainly focused on the classic sensory modalities (Marques, 2006;Pecher et al, 2003;van Dantzig et al, 2008; but see Vermeulen et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…By highlighting the contrast between internal and external perspectives, the present findings extend previous work on the role of perspective in language comprehension, which explored how people construct different perspectives when understanding external events (Borghi et al, 2004;Brunyé et al, 2009;Horton & Rapp, 2003;Morrow et al, 1987;Spivey & Geng, 2001;Wu & Barsalou, 2009). Moreover, by introducing an internal perspective, the present findings extend previous work on switching effects that has mainly focused on the classic sensory modalities (Marques, 2006;Pecher et al, 2003;van Dantzig et al, 2008; but see Vermeulen et al, 2007).…”
Section: Discussionsupporting
confidence: 83%
“…Previous research has found switching costs when properties of verified concepts come from different sensory modalities, rather than from the same sensory modality (Marques, 2006;Pecher, Zeelenberg, & Barsalou, 2003;van Dantzig, Pecher, Zeelenberg, & Barsalou, 2008;Vermeulen, Niedenthal, & Luminet, 2007). For instance, Pecher et al demonstrated that people verify that an apple is shiny more quickly after verifying that a flag is striped than after verifying that an airplane is noisy.…”
mentioning
confidence: 99%
“…This kind of evidence is problematic because the presence of switching costs in conceptual tasks involving different modalities has been used to support the grounded view (e.g., [13][14][15]). For instance, Pecher, Zeelenberg and Barsalou have shown switching effects during a verification task, in which participants are asked whether or not a particular property is true about a given category (e.g., CAT-has a head).…”
Section: The Cross-modal Response Objectionmentioning
confidence: 99%
“…Recent embodied and simulation based approaches to language comprehension predict that comprehension of language triggers mental simulation of events and objects as described in the language [1][2][3][4]. According to theories of embodied cognition [5], such simulation depends upon the mental representations that were formed during comprehenders' actual perceptual experience and interaction with the environment.…”
Section: Introductionmentioning
confidence: 99%